2009
DOI: 10.1134/s0006297909030067
|View full text |Cite
|
Sign up to set email alerts
|

A secreted caspase-3-substrate-cleaving activity at low pH belongs to cathepsin B: a study on primary brain cell cultures

Abstract: The cysteine proteases caspase-3 and cathepsins are involved in both neuronal plasticity and neuropathology. Using primary neuroglial and glial cerebellar cultures, the pH dependence of cleavage of a synthetic caspase-3 substrate, Ac-DEVD-AMC, was studied. At acidic pH, cathepsin B cleaved Ac-DEVD, this activity being significantly higher than that of caspase-3 at pH 7.4. This activity is blocked by peptide inhibitors of both caspase-3 and cathepsin B. Substitution of culture medium for balanced salt solution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Fluorophore-labelled caspase-cleavable probes (for example, DEVD) are also commonly utilized despite reports of differential or attenuated cleavage when compared to physiological caspase substrates as well as activation by non-caspase proteases. 7, 8 Moreover, many laboratories employ additional secondary processing steps (for example, flow cytometry methods to count cells in each well) following the acquisition of high-content live-cell imaging data due to a lack of validated protocols controlling for inter-well plating variability and proliferation changes due to treatments. Collectively, these practices undermine the high-throughput nature of live-cell imagers and are limited by the commercially available reporters.…”
mentioning
confidence: 99%
“…Fluorophore-labelled caspase-cleavable probes (for example, DEVD) are also commonly utilized despite reports of differential or attenuated cleavage when compared to physiological caspase substrates as well as activation by non-caspase proteases. 7, 8 Moreover, many laboratories employ additional secondary processing steps (for example, flow cytometry methods to count cells in each well) following the acquisition of high-content live-cell imaging data due to a lack of validated protocols controlling for inter-well plating variability and proliferation changes due to treatments. Collectively, these practices undermine the high-throughput nature of live-cell imagers and are limited by the commercially available reporters.…”
mentioning
confidence: 99%
“…Under pathological conditions, such as hypoperfusion or ischemia, activation of cell death-related proteases may result in destruction of the cytoskeleton during the early stages of cell demise, which promotes detachment of neurons from their surrounding cells (Böhm, 2003). Furthermore, these enzymes may be secreted by neurons (Onufriev et al, 2009) and cleave their substrates in the extracellular space, thus facilitating migration of cells to the stratum lucidum.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, it has been suggested that the clinical failures of the attempts to selectively deliver drugs to the tumor that has been successful in preclinical models were due to the heterogeneous tumor in human patients while the tumors established in the preclinical models are largely homogeneous (ref). Moreover, Interestingly, DEVD has been reported to be hydrolyzed by cathepsin B at pH 5–6, suggesting that prodrug systems such as ADC that are internalized into the cells by endocytosis could easily take advantage of the STAEPT paradigm by simply replacing the linker with DEVD. In conclusion, we believe that STAEPT could be a promising strategy to improve upon current targeted therapies, especially the ones that exploit cytotoxins as their warhead.…”
Section: Resultsmentioning
confidence: 99%